1995
DOI: 10.1099/0022-1317-76-8-1945
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor induction of human papillomavirus type 16 E6/E7 mRNA in tumour cells involves two AP-1 binding sites in the viral enhancer

Abstract: The early genes E6 and E7 from human papillomaviruses (HPVs) play a key role in the development of cervical cancer. Modulation of E6 and E7 gene expression may alter tumour progression; therefore, modifiers of viral transcription such as hormones or growth factors are potential risk factors in cancer development. We have analysed the effects of epidermal growth factor (EGF) on E6/E7 mRNA from human papiUomavirus type 16 (HPV-16) by Northern blot in two cell lines, SiHa cervical carcinoma cells, and HPK IA, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 75 publications
2
12
0
Order By: Relevance
“…When a 4 bp mutation in the AP-1 motif in the promoter was tested in PC12 cells, the results clearly demonstrated that this motif was required for the induction of the clusterin promoter by both NGF and EGF. Moreover, the mutant gave a weaker basal expression than the wild type, which confirms previous findings that AP-1 sites can contribute to basal promoter activity in the absence of inducers [39,40]. EMSA (' band shift ') studies to identify the protein(s) interacting with the sequence motif demonstrated binding of a factor to the AP-1 motif that was competed for by the homologous sequence and by two other AP-1 sites, including the site from the collagenase promoter, but not by other fragments not containing an AP-1 site.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…When a 4 bp mutation in the AP-1 motif in the promoter was tested in PC12 cells, the results clearly demonstrated that this motif was required for the induction of the clusterin promoter by both NGF and EGF. Moreover, the mutant gave a weaker basal expression than the wild type, which confirms previous findings that AP-1 sites can contribute to basal promoter activity in the absence of inducers [39,40]. EMSA (' band shift ') studies to identify the protein(s) interacting with the sequence motif demonstrated binding of a factor to the AP-1 motif that was competed for by the homologous sequence and by two other AP-1 sites, including the site from the collagenase promoter, but not by other fragments not containing an AP-1 site.…”
Section: Discussionsupporting
confidence: 89%
“…AP-1 activation can also be achieved by the stimulation of protein kinase C with phorbol esters, which elicits an signalling response via the Raf-1\MEK\ERK cascade [24,44]. Most AP-1 binding sites have been functionally tested by phorbol ester stimulation of protein kinase C : only in very few cases have AP-1 sites been characterized as EGF response elements [24,40,45]. It can be assumed, however, that the stimulation of a whole set of genes by EGF, NGF and other growth factors goes through the activation of AP-1.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are multiple AP-1-binding sites within the LCR of the HPV genome ( Fig. 1) (111, 162, 203) that enhance E6/E7 expression (discussed below) (111,136,147,162). Moreover, AP-1 contributes significantly to HPVmediated carcinogenesis (119), and the composition of AP-1 clearly changes during the course of the transformation process (170,197).…”
Section: Free Zinc Ions and The Papillomavirusesmentioning
confidence: 99%
“…Also, Meyers et al [1997] demonstrated these additional HPV-18 splice sites by studying HCK keratinocyte cell lines carrying episomal HPV-18: donor site at nucleotide 233 and acceptor site at nucleotide 2779 resulting in the deletion of E6, E7, and E1 ORFs; and donor site at nucleotide position 929 and acceptor site at nucleotide position 3434 resulting in the deletion of E1 and part of E2. An explanation proposed by Peto et al [1995] for a single band having to account for transcripts of different sizes is that bands migrating near the ribosomal RNA are not separated due to compression by the ribosomal RNA.…”
Section: Discussionmentioning
confidence: 98%